Characterization of foam materials based on HDPE plastic waste for automotive seat application - rahman, yazid; Noraini Marsi (Progress in Engineering Application and Technology, 2021)
The NVH problem is one of the main worries of car manufacturers. Moreover, the problems of seeking alternate methods for the disposal of large quantities of packaging are rising for organizations. This study therefore suggests a method of solid-state recycling to incorporate direct recycling of polyethylene as the green engineering shaping technology. This study aims to determine optimum composition of HDPE plastic waste reinforced PU foam for automotive seat application. Using HDPE reuse can offer new options for a smoother, quieter driving experience, and it will address the problem with materials that compromise overall vehicle weight. Plastic wastes of high-density polyethylene (HDPE) are prepared for various ratios of 0.2, 0.4, 0.6 and 0.8. The mechanical test was carried out using tests of Tensile strength test (ASTM D3574), Impact strength test (ASTM D3574), Sound absorption test (ASTM E105-95) and Bending strength test (ASTM C293). For physical test Optical Microscopic test (ASTM F728-81) and porosity testing was performed. The result show that the highest strength of the tensile and bending strength is 0.08 MPa respectively and 0.10 MPa. Moreover, data have shown that in the O.2:1:1, 0.4:1:1 and 0.8:1:1 ratio of the study, the maximum impact intensity test used was same at 1.06 kJ/m2. Sample a obtained the highest sound absorption coefficient of between 1200Hz and 1400Hz with a ratio of 0.2:1:1 with the highest sound absorption coefficient (SAC) of 0.61. Insulation foams were also examined in an optical microscope and found to be changed according to an increasing ratio from plastic to PUF in white, uniform morphological shape and cellular form.